2020
DOI: 10.1186/s12885-020-07624-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of dosimetry distribution for patients with multiple brain metastases from non-small cell lung cancer by a Cyberknife stereotactic radiosurgery (SRS) system

Abstract: Background In order to obtain a high dose conformal index of tumor and steep dose fall-off in healthy tissues for brain metastasis stereotactic radiosurgery (SRS), the aim of this study was to investigate SRS planning optimization by comparing one multiple-lesions plan (MLP) with multiple single-lesion plans (SLPs) for patients with multiple brain metastases using the Cyberknife (CK) system. Methods Fifty non-small cell lung cancer (NSCLC) patients (28 males and 22 females) with 2–4 brain metastases, inter-tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Yu et al, while finding the CI value similar for both plans, Uzel reported that the plan made separately for each metastasis is more advantageous in terms of CI. In our result, it was found that separately treatment planning was more advantageous in terms of CI, in line with Uzel [19,20]. In our result, it was found that separately treatment planning was more advantageous in terms of CI, in line with Uzel Likewise, it was concluded that it was more appropriate to plan separately according to the nCI values.…”
Section: Discussionsupporting
confidence: 81%
“…Yu et al, while finding the CI value similar for both plans, Uzel reported that the plan made separately for each metastasis is more advantageous in terms of CI. In our result, it was found that separately treatment planning was more advantageous in terms of CI, in line with Uzel [19,20]. In our result, it was found that separately treatment planning was more advantageous in terms of CI, in line with Uzel Likewise, it was concluded that it was more appropriate to plan separately according to the nCI values.…”
Section: Discussionsupporting
confidence: 81%
“…This fractionated approach allows for the delivery of effective doses to the multiple-target while minimizing damage to surrounding healthy brain tissue [ 5 , 6 ]. Various techniques, including the use of conventional linear accelerator (LINAC), Gamma Knife (Elekta AB, Stockholm, Sweden), and CyberKnife (Accuray, Sunnyvale, CA), have been employed for SRS/fSRS [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic radiosurgery (SRS), such as single-fraction or hypofractionated (two to five fractions) cranial radiosurgery, is commonly used to treat various primary and metastatic brain tumors ( 1 ). Compared with other modern SRS treatment equipment, including different types of linear accelerators and Gamma Knife, the frameless image-guided radiosurgery system CyberKnife (CK) can deliver a high conformal dose to the tumor accurately and spare normal brain tissue ( 2 6 ). To make it easier and more convenient to contour the target, the patient is often injected with a contrast agent (CA) when CT scanning is performed ( 7 ).…”
Section: Introductionmentioning
confidence: 99%